2022
DOI: 10.3389/fmicb.2022.846857
|View full text |Cite
|
Sign up to set email alerts
|

Synergism Among the Four Tobacco Bushy Top Disease Casual Agents in Symptom Induction and Aphid Transmission

Abstract: Tobacco bushy top disease (TBTD), caused by multiple pathogens including tobacco bushy top virus (TBTV), tobacco vein distorting virus (TVDV), TBTV satellite RNA (TBTVsatRNA), and TVDV-associated RNA (TVDVaRNA), is a destructive disease in tobacco fields. To date, how these causal agents are co-transmitted by aphid vectors in field and their roles in disease symptom induction remain largely unknown, due mainly to the lack of purified causal agents. In this study, we have constructed four full-length infectious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…Our results show that CMoV appears to be a driver of symptom development when co-infected with TuYV and/or Sigma or ST9. CMoV also facilitated the systemic movement of all three tlaRNAsalbeit with differing efficiencies-in the absence of TuYV, corroborating the results of a recent study that demonstrated umbravirus-facilitated tlaRNA systemic movement in the tobacco bushy top disease (TBTD) complex (Chen et al, 2022).…”
Section: Open Access Edited Bysupporting
confidence: 85%
See 2 more Smart Citations
“…Our results show that CMoV appears to be a driver of symptom development when co-infected with TuYV and/or Sigma or ST9. CMoV also facilitated the systemic movement of all three tlaRNAsalbeit with differing efficiencies-in the absence of TuYV, corroborating the results of a recent study that demonstrated umbravirus-facilitated tlaRNA systemic movement in the tobacco bushy top disease (TBTD) complex (Chen et al, 2022).…”
Section: Open Access Edited Bysupporting
confidence: 85%
“…Japonica), only CMoV and the CRLVaRNA could be detected in the recipient plant, making this the first reported evidence that an umbravirus may support tlaRNA systemic movement in the absence of a co-infecting polerovirus, although these results could also have other potential explanations. In another recent study by Chen et al (2022), after co-agroinoculation of infectious clones of the umbravirus tobacco bushy top virus (TBTV) with the tobacco vein distorting virus associated RNA (TVDVaRNA) the authors could detect the TVDVaRNA along with TBTV in the distal non-inoculated leaves, thereby confirming an umbravirus could independently support tlaRNA systemic movement. Here, we present data demonstrating that CMoV was able to support systemic movement of all three tlaRNAs (Gamma, Sigma, ST9), however this interaction appeared to be less efficient in co-infections with Gamma, suggesting some degree of specificity in these umbravirus-tlaRNA interactions.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Vectors play vital roles in viral long-distance transmission and prevalence [30]. This study identified aphid-borne viruses CMV [31], ChiVMV [32], TVDV [33], and PLRV [34], as well as thrips-borne TSWV [35], infecting A. carmichaelii plants. Potyviruses [36], certain cheraviruses [19], and the majority of carlaviruses [37] are transmitted by aphids.…”
Section: Members Of Potyvirusmentioning
confidence: 99%
“…Regarding the viruses detected in A. carmichaeli, it is well-documented that CMV [38], ASGV [39,40], ChiVMV [41], PLRV [34], TVDV [33,42], and TSWV [38] have the ability to infect other economically important crops. The findings reported in this study suggest that the host range of these viruses is expanding.…”
Section: Members Of Potyvirusmentioning
confidence: 99%